Nitrogen deposition reduces biodiversity but strengthens plant–microbe interactions - Zonghao Hu; Yi Fan; Junjie Yang; Shuang Pang; Rong Mao; Yang Zhang; Xingguo Han; Ximei Zhang (Geoderma)
Nitrogen deposition can reduce plant and soil microbial diversity, and thus, it was traditionally thought to decouple plant–microbe interactions. However, few studies quantified these interactions directly and systematically. Here, we conducted a long-term nitrogen deposition experiment with nine rates (0–50 g nitrogen m−2 yr−1) in the Eurasian steppe. Although nitrogen addition reduced biodiversity, it strengthened the relationships between plant and microbial community indices (biomass, richness, and composition) in a structural equation model, increased the Pearson’s correlation coefficient (r) between plant biomass and microbial biomass, and also increased the density of the plant–microbe interaction subnetwork. These results challenge the traditional decoupling viewpoint and indicate that plant–microbe interactions strengthen to adapt to increasing nitrogen deposition pressure.